2D in-plane Hall Sensing Based on a New Microdevice Coupling Concept. (2015) - Lozanova, S.V.; Noykov, S.A.; Ivanov, A.J.; Roumenin, Ch.S.
Abstract: A 2D Hall microdevice for synchronous measurement of two in-plane magnetic-field components, using an original coupling concept based on two identical parallel-field three-contact (3C) silicon Hall elements positioned at right angle and integrated on the same chip, is presented. The two pairs of outer contacts of 3C Hall transducers are connected via two load resistors, converting simultaneously and independently the current changes in B x and B y magnetic fields into Hall voltages. Since the supply currents in both structures are equal, the magnetosensitivities are the same, too. At a fabrication of the devices on a common silicon chip, the output temperature drifts are perfectly matched. The high measurement accuracy, performance and compensated channel offsets of this 2D magnetometer are achieved by the minimal interface components between both sensors. The suggested sensing microsystem is appropriate for many contactless measurement instruments.